REGIONAL AND INTERNATIONAL INFLUENCES ON THE TRANSFER OF POWER DURING THE MAMLUK ERA IN IRAQ (1750–1831) - Alyousif, Awrad A.; Hassan, Dherar K. (Veredas do Direito, 2026)
The transfer of power and the role of regional and international interventions in Iraq during the Mamluk period (1750–1831). In particular, this project analyses how local authority has combined with Ottoman legitimacy and international interventions. The study shows that the Mamluk political system was characterized by the exercise of effective power through military control and alliances with local elites tribal groups rather than functioning as part of the Ottoman state administrative apparatus which was legitimised by the issuance of imperial decrees by the latter. The results further reveal that the Persian and European interventions, in particular those originating from Britain and France, were a determining factor for bolstering certain rulers. Thus, every power transfer emerged as a layered negotiation involving basic recognition at the centre and differential expression of complicity. The fragile equilibrium resulted in chronic political instability, a weakening of military and administrative institutions, and a form of deferred legitimacy based on regional and local power equilibria rather than on imperial authorization. These dynamics ultimately led to the collapse of Mamluk rule and the reassertion of direct Ottoman authority in 1831. Thus, the interpretation suggests that this integrated the internal structures of Mamluk Iraq. Regional and international influences are linked to the causes of instability and the deterioration of the ruling elite’s relative autonomy.